Reliability-Centered Maintenance of Rapier Dragline for Optimizing Replacement Interval of Dragline Components - Palei S.K.; Das S.; Chatterjee S. (My University, 2025)
Machine manufacturers’ recommendations on maintenance strategies of capital-intensive draglines are not always based on real data and therefore lead to losses from downtime. This paper proposes a preventive maintenance strategy for a dragline deployed in an opencast coal mine based on reliability-centered maintenance and failure-mode-effects analysis using real operational data. Reliability-centered maintenance replaced a cluster of critical failure components of the dragline while satisfying two specific conditions: (i) the components should be replaced at the earliest mean time to failure (MTTF) within the group and (ii) the time taken to replace all the parts should be equivalent to the maximum downtime within the group. Estimated threshold weightage factor identified twenty-six critical failure components for the preventive maintenance strategy, and clustering of components divided them into nine groups. In a group, the loss that is expected to occur by replacing some of the components before their failure, and the gain by reducing the overall maintenance downtime, has been explained through a cost-benefit analysis. The total net profit generated is calculated as US$200,178. This clustering activity also led to a reduction of annual downtime by 231 h, whose approximate market price as equivalent coal production costs $295,365. © 2020, Society for Mining, Metallurgy & Exploration Inc.